Adaptive motion coordination of passive systems under quantization effect. (13th March 2014) - Fu, Junjie; Wang, Jinzhi
Summary In this paper, we consider the quantization effect on an adaptive motion coordination control law for passive multi‐agent systems when the time‐varying reference velocity is only available to the leader. Both logarithmic quantizers and uniform quantizers are investigated. Using tools from nonsmooth analysis and the Barbalat lemma, we prove that with undirected connected communication graphs, coordination problem is still solvable when logarithmic quantizers are used and the parameter convergence is also guaranteed when the basis functions satisfy certain persistently exciting property. When uniform quantizers are used, we prove that practical consensus can be achieved, and both the bounds of the consensus error and the velocity tracking error are proportional to the parameter of the quantizer. Simulation examples are provided to illustrate the results. Copyright © 2014 John Wiley & Sons, Ltd.